Use of culturally-inspired materials as models: Effects on learning solids in geometry - Abo, Jehad A.; Abdul Latip, Faiza M.; Mantawil, Tamano S. (Edelweiss Applied Science and Technology, 2026)
The research examined the impact of culturally-inspired materials on Grade 8 students' performance in Geometry at Mindanao State University, Maguindanao Integrated Laboratory Science High School. It sought to compare pre-test and post-test performances of students taught with culturally-inspired materials with those taught using the Lecture and Discussion Approach. The experimental group (49 students in Section C) employed culturally-inspired materials, whereas the control group (47 students in Section D) utilized conventional approaches. An experimental design was employed, utilizing researcher-developed questionnaires, surveys, and a rubric for collaborative problem solving. Statistical analysis employed frequency counts, percentages, means, standard deviations, paired t-tests, and independent t-tests. Results indicated that 65.31% of experimental group students exhibited low performance in the pre-test. Yet, post-test results indicated that the use of culturally-inspired materials significantly enhanced student performance and learning capabilities compared to conventional methods. The majority of students reacted positively to this, and their products were of higher scores, with a mean of 17 out of 20. Training for mathematics teachers on the use of culturally-inspired materials in lessons, particularly in teaching solids in Geometry, was recommended in the study. It also proposed incorporating this strategy into the secondary school mathematics curriculum to make learning more meaningful, relevant, and interesting.